Measuring and Analysing the Financial Performance of State-Owned Economic Entities - Kistóth, Krisztina (Public Finance Quarterly, 2021)
The experts of the State Audit Office of Hungary analysed financial performance measurement issues of state-owned companies (public companies) with the aim to apply the principle of performance as widely as possible during public money spending. In many respects, the same tools can be used to measure and analyze the performance of these companies as for private sector companies, however misrepresentations arising from public sector specialties must be filtered out. Therefore, an adjusted version of the financial indicators has been prepared, using corrective items specifically focusing public sector specificities. To test the adjusted indicators, we prepared an analysis for a group of 148 public companies, the main findings of which are presented in our article. The special conditions, operation or risks of state-owned companies may require different tools and priorities in terms of ownership control. In this article, we try to form relatively homogeneous groups, portfolios - based on adjusted financial indicators- which helps the owner to treat groups of companies differently according to financial capabilities and performance. Classification into groups can draw attention to critical management factors, risks, but also strengths as well. In this way, the development of portfolios can provide a good basis for effective ownership management of companies.